Comparative Study of World Urban Farming Practices: Efforts to Support Food Security and Environmental Conservation - Indra Jaya Wiranata (Jurnal Hubungan Internasional Indonesia, 2025)
Accelerated urbanization, climate change, and rising food insecurity have led cities to adopt urban agriculture to improve food systems and support environmental sustainability. This study provides a comparative analysis of urban agriculture practices in seven countries: Iran, the United Kingdom, Argentina, South Korea, Singapore, Zimbabwe, and New Zealand. It examines how these practices contribute to food security and environmental conservation. Methods like community gardens, rooftop and vertical farming, permaculture, and community agroecology differ across contexts. They reflect varying levels of government support, ranging from strong policy-driven models in Singapore and South Korea to community-led initiatives in Zimbabwe and Iran. Urban agriculture plays a significant role in food security, especially in regions vulnerable to food shortages and in national food strategies. It also offers environmental benefits, including the creation of green spaces, climate mitigation, urban heat reduction, resource conservation, and improved biodiversity. The findings, based on a literature review of academic studies, policy reports, and case studies, show that the success of urban agriculture hinges on its fit with local conditions, support from policy frameworks, and its integration into broader sustainable development approaches. This positions urban agriculture as an important tool for building resilient urban food systems.